Real-Time Random Number Generation with Ring Oscillator Based Double Physically Unclonable Function - Tuncer, Seda Arslan (Soc Microelectronics, Electron Components Materials-Midem, 2018)
Integrated Circuit (IC) is a semiconductor wafer that is fabricated for millions of components. Although it is accepted that the same chemical properties are observed in the same type of ICs produced within the processes of wafer production, masking, etching, doping, atomic diffusion, ion implantation, metallization and packaging steps, these properties differ at microscopic levels. For example, the propagation delay is different in two logic elements in the same integrated circuit, and the silicon distribution in each LE is not equal. These differences have created the concept of Physically Unclonable Function (PUF). PUF is a function that creates values specific to the physical environment in which it operates. This article presents the implementation of a ring oscillator- (RO) based PUF design in two different ICs to generate random numbers. Two different FPGA (Field Programmable Gate Array) cores were used in the proposed structure, and PUF structures were implemented on these hardware elements. The raw random numbers obtained by the generated system were post-processed to be used in applications (e.g. encryption, game programming). The study used Von Neumann and hash functions for post-processing. NIST and Autocorrelation tests were also administered to check the validity of the obtained random numbers.
Keywords: Random number generation; Field programmable gate arrays; physically unclonable function